Ethical Leadership, Ethical Culture, Voice Behaviour, And Employee Performance - Mahendra, Ajna Cakra Bayu; Qamari, Ika Nurul; Roni, Mastura (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
Employees are required to maintain positive interactions with one another in the workplace. This study advances the conversation of ethical leadership and ethical culture on employee performance, with voice behavior as a mediator. This study distributed 350 questionnaires to construction company employees in Bantul, Indonesia, and obtained a 153-response rate (43.71%). Structural equation modeling with Amos software is used to analyze the coded information. This study found a substantial link between ethical leadership, ethical culture, and voice behavior in increasing employee performance. Furthermore, voice behavior was discovered to mediate in both relationships. The finding implies a critical need to maintain positive conversations inside firms as they are part of job satisfaction indicators.